(SBAVLMFV AU[FV V[FELAVJV OF XR (BSOLIDWORKSs - (SBga(Suyxjw Fooga(Spryjns; (SVxga(Syursrynry Vrzlgas ((SAyxrfmervjs)
(SV[FELAVJ VF SAUAOFXULMR NRDLVOLMR SURDUAOOA (BCAD (SV[FELAVJ (B2D (SV[JOAX]P V[FELAVJ (B3D (SV[JOAX]P V[FELAVJ VYPAUORNRDJOAX]P FMSRPJVJ OJ[APRNRDLM]P V[FEL]Ps
(SV[FELAVJ VF SAUAOFXULMR NRDLVOLMR SURDUAOOA (BCAD (SV[FELAVJ (B2D (SV[JOAX]P V[FELAVJ (B3D (SV[JOAX]P V[FELAVJ VYPAUORNRDJOAX]P FMSRPJVJ OJ[APRNRDLM]P V[FEL]Ps